Singiel i singielka o życiu w pojedynkę (dokument dostępny po zalogowaniu tylko dla osób z dysfunkcją wzroku) - Czernecka, Julita (Warszawa: Polska Akademia Nauk)
The article presents Polish singles` main arguments for living alone that are from micro-social level, e.g. unfortunate experiences in previous relationships, negativememory of one`s parents relationship, very strong family ties, negative impression of friends` relationships, no experience in building lasting relationships, happy marriage of one`s parents as an unachievable ideal, living alone as a natural consequence of being an only child etc.
Keywords: singiel; single; living alone; życie w pojedynkę; samotność z wyboru; alone by choice